COVID-19 and Cushing's disease in a patient with ACTH-secreting pituitary carcinoma. (28th February 2022) - de Filette, J M K; Sol, Bastiaan; Awada, Gil; Andreescu, Corina E; Unuane, David; Aspeslagh, Sandrine; Poelaert, Jan; Bravenboer, Bert
Abstract : Summary: The pandemic caused by severe acute respiratory syndrome coronavirus 2 is of an unprecedented magnitude and has made it challenging to properly treat patients with urgent or rare endocrine disorders. Little is known about the risk of coronavirus disease 2019 (COVID-19) in patients with rare endocrine malignancies, such as pituitary carcinoma. We describe the case of a 43-year-old patient with adrenocorticotrophic hormone-secreting pituitary carcinoma who developed a severe COVID-19 infection. He had stabilized Cushing's disease after multiple lines of treatment and was currently receiving maintenance immunotherapy with nivolumab (240 mg every 2 weeks) and steroidogenesis inhibition with ketoconazole (800 mg daily). On admission, he was urgently intubated for respiratory exhaustion. Supplementation of corticosteroid requirements consisted of high-dose dexamethasone, in analogy with the RECOVERY trial, followed by the reintroduction of ketoconazole under the coverage of a hydrocortisone stress regimen, which was continued at a dose depending on the current level of stress. He had a prolonged and complicated stay at the intensive care unit but was eventually discharged and able to continue his rehabilitation. The case points out that multiple risk factors for severe COVID-19 are present in patients with Cushing's syndrome. 'Block-replacement' therapy with suppression of endogenous steroidogenesis and supplementation of corticosteroid requirements might be preferred in this patient population. Learning points: Comorbidities for severe coronavirus disease 2019 (COVID-19) are frequently present in patients with Cushing's syndrome. 'Block-replacement' with suppression of endogenous steroidogenesis and supplementation of corticosteroid requirements might be preferred to reduce the need for biochemical monitoring and avoid adrenal insufficiency. The optimal corticosteroid dose/choice for COVID-19 is unclear, especially in patients with endogenous glucocorticoid excess. First-line surgery vs initial disease control with steroidogenesis inhibitors for Cushing's disease should be discussed depending on the current healthcare situation.